2023
DOI: 10.1186/s40623-023-01883-8
|View full text |Cite|
|
Sign up to set email alerts
|

The sequence of the 2017–2018 eruptions and seismo-acoustic activity at Kirishima volcano group

Mie Ichihara,
Tsukasa Kobayashi,
Fukashi Maeno
et al.

Abstract: Kirishima volcano consists of more than 20 eruptive centers. Among them, Shinmoe-dake had magmatic eruptions in October 2017 and March 2018. Subsequently, another active cone, Iwo-yama, had phreatic eruptions in April 2018. These events were unique in that the 2018 eruption was the first effusion-dominated eruption of Shinmoe-dake and the first simultaneous activity of two cones of the Kirishima volcanic group ever documented. We report the detailed sequence of the events by combining areal photos, satellite i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, no signi cant increase in volcanic earthquakes was identi ed for several months before the 2017 eruption (Yamada et al 2019). Ichihara et al (2023a) suggested that the increasing magnitude of the seismic background noise since early 2017 is due to the degassing from the magma within the conduit. Therefore, we have identi ed no robust supporting evidence for the material withdrawn preceding the 2017 eruption.…”
Section: Potential Mechanisms For the Precursory Deformationmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, no signi cant increase in volcanic earthquakes was identi ed for several months before the 2017 eruption (Yamada et al 2019). Ichihara et al (2023a) suggested that the increasing magnitude of the seismic background noise since early 2017 is due to the degassing from the magma within the conduit. Therefore, we have identi ed no robust supporting evidence for the material withdrawn preceding the 2017 eruption.…”
Section: Potential Mechanisms For the Precursory Deformationmentioning
confidence: 99%
“…In contrast, the GNSS baselines turned to extension after the early stage of the eruption (Yamada et al 2019). The lava was ejected from the vent from the east side of the crater after the ash emission phase and covered the pre-existing lava dome, which was formed during the 2011 eruption (Additional File 1: Figure S1; Ichihara et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations